Analisis Faktor Penentu menjadi Nasabah Bank Syariah: Perbandingan Segmen BPR Syariah dan Bank Umum/Unit Usaha Syariah di Sumatera Barat - Yasri, Yasri (Jurnal Kajian Manajemen Bisnis, 2012)
The objective of this research is to analyze factors that determine customer segments of BPR syariah and Syariah General Bank. This research conducted on two groups of customer as population; BPR syariah and Syariah General Bank. BPR syariah are represented by the customers of BPR Makmur Syariah in 50 kota Payakumbuh and BPR Syariah Barakah Nawaitul Ikhlas in Solok. While the syariah general bank are represented by the customers of Bank  Mandiri Syariah and syariah business unit of Bank Nagari (BPD). Sampling technique is judgment sampling  by considering age, gender and customers business. Sample size of each segment is 70 respondents. Sample of each syariah bank is 35 respondents. Methods of data analysis is  Analytical Hierarchy Process (AHP). The research found that both of segments are considering the compliance on Islamic rule and this factor was ranked first. However, the proximity of the location factor, financial gain, and service quality has different rank ofimportance between two segments.